Systems-Approach to the Study of Subject Headings - Neelameghan, A. (Journal of Information and Knowledge, 1974)
The helpfulness of adopting systems-approach to the study of the design of a Subject Heading System for a Document Finding System (=DFS), is illustrated. The objective, structure, and function of Subject Heading System iS conditioned by the context of the DFS Holistic view of the design of Subject Heading System aims to achieve maximum output for an input into the system. The Design of Subject Heading System can be done in three planes of work. The essential feature In the structure of a subject and itS implications to the design of subject heading system are briefly discussed.